Molecular Characterization of Inflammatory Myofibroblastic Tumors with Frequent ALK and ROS1 Fusions and Rare Novel RET Gene Rearrangement - Antonescu, Cristina R (Am J Surg Pathol, 2015)
Approximately 50% of conventional IMTs harbor ALK gene rearrangement and overexpress ALK. Recently gene fusions involving other kinases have been implicated in the pathogenesis of IMT, including ROS1 and in one patient PDGFRB. However, it remains uncertain if the emerging genotypes correlate with clinicopathologic characteristics of IMT. In this study we expand the molecular investigation of IMT in a large cohort of different clinical presentations and analyze for potential genotype-phenotype associations. Criteria for inclusion in the study were typical morphology and tissue availability for molecular studies. The lack of ALK immunoreactivity was not an excluding factor. As overlapping gene fusions involving actionable kinases are emerging in both IMT and lung cancer, we set out to evaluate abnormalities in ALK, ROS1, PDGFRB, NTRK1 and RET by FISH. Additionally, next generation paired-end RNA sequencing and FusionSeq algorithm was applied in 4 cases, which identified EML4-ALK fusions in 2 cases. Of the 62 IMTs (25 children and 37 adults), 35 (56%) showed ALK gene rearrangement. Of note, EML4-ALK inversion was noted in 7 (20%) cases, seen mainly in the lung and soft tissue of young children including 2 lesions from newborns. There were 6 (10%) ROS1 rearranged IMTs, all except one presenting in children, mainly in the lung and intra-abdominal and showed a distinctive fascicular growth of spindle cells with long cell processes, often positive for ROS1 IHC. Two of the cases showed TFG-ROS1 fusions. Interestingly, one adult IMT revealed a RET gene rearrangement, a previously unreported finding. Our results show that 42/62 (68%) of IMTs are characterized by kinase fusions, offering a rationale for targeted therapeutic strategies. Interestingly 90% of fusion negative IMT were seen in adults, while >90% of pediatric IMT showed gene rearrangements.EML4-ALK inversion and ROS1 fusions emerge as common fusion abnormalities in IMT, closely recapitulating the pattern seen in lung cancer.